Microbiologia básica de Leptospira spp.: uma ferramenta para melhorar estudos sobre leptospirose (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Introduction: Leptospirosis is a zoonosis with a high incidence worldwide, caused by spirochetes belonging to the genus Leptospira. The maintenance of the strains and the in vitro growth of the microorganism remain time-consuming and difficult to be performed. Demonstrating the need to optimize laboratory culture techniques, towards improving studies in leptospirosis.